Możliwości zastosowania kannabinoidów w leczeniu jaskry - Nadolska, Krystyna; Goś, Roman (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Over a period of several decades numerous scientific research has proven that, regardless of the route of administration, cannabinoids are able to decrease intraocular pressure. What is more, these compounds are characterized by neuroprotection and vasodilatation properties, that additionally substantiate it’s therapeutic utility in conservative treatment of glaucoma. So far, it has not been described in details what mechanism is used to lower the intraocular pressure by cannabinoids. Nevertheless, the presence of endocannabinoid receptors in structures of the eye responsible for formation and outflow of aqueous humor is an explanation for effectiveness of these compounds, when administered in topical form. These days, with the aid of modern pharmacological technology are available significantly bigger possibilities of improving bioavailability of cannabinoids administered to the eye than in the past, as well as limitation of it’s undesired side effects.